Vesico‐urethral anastomosis sampling: a forgotten tool for guiding salvage radiation after radical prostatectomy. (10th May 2021) - Timm, Brennan; Farag, Matthew; Liodakis, Peter; Angus, David; Lim Joon, Daryl; Bolton, Damien
Abstract : Objective: To review the utility of vesicourethral anastomosis (VUA)‐directed biopsy in the setting of biochemical recurrence (BCR) after radical prostatectomy (RP) for prostate cancer (PCa) in patients who have undergone evaluation by gallium‐68 prostate‐specific membrane antigen positron emission tomography with computed tomography ( 68 Ga‐PSMA PET/CT). Methods: We completed a retrospective review of a prospectively maintained dataset from January 2015 to August 2020. Patient demographics were recorded for those who experienced BCR, as defined by a rise in prostate‐specific antigen (PSA) level to above 0.2 ng/mL, who had a 68 Ga‐PSMA PET/CT that did not demonstrate recurrence within the prostate bed, and who subsequently underwent a transperineal ultrasonography (TPUS)‐guided biopsy directed at the VUA. Histological reporting of the biopsies was undertaken in order to determine whether the benefits of salvage radiation therapy (SRT) could be justified by the presence of cancer cells. Results: Eighteen patients who had a 68 Ga‐PSMA PET/CT and underwent VUA‐directed biopsy were identified as having BCR. 68 Ga‐PSMA PET/CT scans demonstrated avidity at the VUA in none of the patients, although two out of 18 patients showed avidity in the seminal vesicles and two out of 18 patients showed avidity within regional lymph nodes. Histology from the TPUS‐guided, VUA‐directed biopsies demonstrated no prostatic tissue in six out of 18 and presence of prostatic tissue in 12 out of 18 of patients, respectively. In 7 out of 18 cases, there was histological evidence of recurrent PCa at the VUA in the absence of a positive 68 Ga‐PSMA PET/CT scan. Conclusion: This study highlights the potential value of VUA‐directed biopsy. We are reminded that a negative 68 Ga‐PSMA PET/CT does not exclude local recurrence and that the addition of a VUA‐directed biopsy may aid in the decision‐making process for patients with BCR following RP, especially when 68 Ga‐PSMA PET/CT is locally negative. When the result of both 68 Ga‐PSMA PET/CT and VUA‐directed biopsy are negative, it should encourage clinicians to share decision‐making in regard to undertaking SRT vs continuing BCR surveillance. This may delay the possible side effects associated with SRT, despite its excellent PSA failure‐free survival rate.